Analiza gibanja ventilske opruge - Ivan Mahalec (Promet - Traffic&Transportation, 1970)
The paper considers the surge of a spring, retained at oneend and controlled by a cam at the other end. The periodic liftfunction of the cam was approximately replaced by the Fourierpoly nom. The forced displacement amplitudes were determinedfor each harmonic of this poly nom. The theory of forced longitudinal vibrations of a bar with continuously distributed mass,elasticity and dumping was applied to simulate the motion ofspring coils. It was found out that two or more modes may consistconcurrently in the spring. This was obtained by analyzingmathematical formulas and by comparing computed and publishedmeasured results. The line spectrum of the Fourier serieswas introduced as a useful tool for estimating the influence ofthe high order harmonics on the spring surge.